2023
DOI: 10.3847/1538-4357/acdc27
|View full text |Cite
|
Sign up to set email alerts
|

MIDIS: Strong (Hβ+[O iii]) and Hα Emitters at Redshift z ≃ 7–8 Unveiled with JWST NIRCam and MIRI Imaging in the Hubble eXtreme Deep Field

Abstract: We make use of JWST medium-band and broadband NIRCam imaging, along with ultradeep MIRI 5.6 μm imaging, in the Hubble eXtreme Deep Field to identify prominent line emitters at z ≃ 7–8. Out of a total of 58 galaxies at z ≃ 7–8, we find 18 robust candidates (≃31%) for (Hβ + [O iii]) emitters, based on their enhanced fluxes in the F430M and F444W filters, with EW0(Hβ +[O iii]) ≃87–2100 Å. Among these emitters, 16 lie in the MIRI coverage area and 12 exhibit a clear flux excess at 5.6 μm, indicating the simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Deep photometric investigations have also confirmed the monotonic increase in the merger rate until z = 6 (Duncan et al 2019). We hypothesize that the increased merger rate might be responsible for the overabundance of EELGs detected with JWST at z > 6 (Cameron et al 2023;Endsley et al 2023;Rinaldi et al 2023;Tang et al 2023). Thus, properly accounting for mergers would be important while estimating physical properties of gas and stars, in particular their kinematics and morphology in the early Universe.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Deep photometric investigations have also confirmed the monotonic increase in the merger rate until z = 6 (Duncan et al 2019). We hypothesize that the increased merger rate might be responsible for the overabundance of EELGs detected with JWST at z > 6 (Cameron et al 2023;Endsley et al 2023;Rinaldi et al 2023;Tang et al 2023). Thus, properly accounting for mergers would be important while estimating physical properties of gas and stars, in particular their kinematics and morphology in the early Universe.…”
Section: Discussionmentioning
confidence: 79%
“…In the past decade, deep photometric surveys with Spitzer and Hubble Space Telescope (HST) revealed more than two orders increase in the [O III] 5007+Hβ equivalent width (EW) of galaxies between z = 0 and 6 (Labbé et al 2013;Roberts-Borsani et al 2016;Barro et al 2019;Mainali et al 2019;Endsley et al 2020;Gupta et al 2022). Direct observations with the James Webb Space Telescope (JWST) in the past year have confirmed that 80% of galaxies have [O III] 5007+Hβ EW >800 Å; almost 3 times the EW of a typical star-forming galaxy at z ∼ 2 (Cameron et al 2023;Endsley et al 2023;Rinaldi et al 2023;Tang et al 2023). Thus, understanding the physical origin of extreme emission lines is becoming increasingly important to understand the early galaxy evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The left and right panels of Figure 4 illustrate several important points about our sample of EELGs. First, a visual inspection of the left panel of Figure 4 shows that our sample reproduces the known anticorrelation between rest-frame EW(Hα) and stellar mass (e.g., Onodera et al 2020;Matthee et al 2023;Rinaldi et al 2023). However, there does not appear to be any correlation .…”
Section: Dependence Of Equivalent Widths On Physical Properties and R...mentioning
confidence: 75%
“…Early JWST studies of EELGs have already begun to yield interesting results. These include the identification of very high EW systems (EW >1000 Å for [O III] + Hβ and Hα) up to z ∼ 9 and confirmation that EELGs are common in the high-z Universe (e.g., Kashino et al 2023;Laporte et al 2023;Matthee et al 2023;Rinaldi et al 2023;Williams et al 2023). Other work has shown that the hydrogen-ionizing photonproduction efficiencies (ξ ion ) of high-z EELGs are generally high, as expected if these objects are responsible for reionization (e.g., Asada et al 2023;Sun et al 2023).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation